Inovasi Metode Pembelajaran Perspektif Hadis dalam Kitab Ar-Rasūl al-Mu’allim wa Asālibuhu fī al-Ta‘līm Karya Abdul Fattah Abu Ghuddah - Kaimudin Kaimudin; Nurhasan Nurhasan; Slamet Priyadi (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to explore innovative learning methods derived from the perspective of the Prophet Muhammad's hadith through an in-depth analysis of Abdul Fattah Abu Ghuddah's book Ar-Rasūl al-Mu'allim wa Asālibuhu fī al-Ta'līm. As the main reference work, this book codifies the Prophet's teaching methods that have been proven to be pedagogically effective. The research uses a qualitative approach with an exploratory-analytical library research method. Primary data was obtained from the book, while secondary data came from reputable journal articles discussing Islamic educational innovation, hadith-based learning methods, and Abu Ghuddah's thoughts. The results of the study show that Abu Ghuddah successfully mapped at least ten main methods of innovative learning sourced from the Prophet's sunnah: 1. Dialogical (Hiwār) and Question and Answer Methods: From Monologue to Interaction. 2. Parable (Amtsāl) and Contextual Analogy (Abstraction to Concreteness) Methods. 3. The Story Method (Qasas) with an Emotional and Reflective Approach. 4. The Habituation and Repetition Method (Tikrār) with Variations: Towards Mastery Learning. 5. The Practical Demonstration Method (al-Tathbīq al-‘Amalī) and Learning by Doing. 6. Differentiated Instruction Method (Ta'līm Fardī): Accommodating Diversity and Individual Responsiveness. 7. Method of Using Media and the Surrounding Environment (al-Ittikhādz al-Wasā'il wa al-Bī'ah). 8. Positive Reinforcement Method (al-Ta'zīz) and Wise Correction (al-Tashhīḥ al-Hakīm). 9. Method of Giving Examples and Role Models (al-Uswah al-Hasanah). 10. Method of Simplification and Staging (al-Tadrīj wa al-Tabsīth). Analysis of these findings in the context of contemporary education reveals that these methods are not only relevant but also contain innovative principles such as student-centered learning, contextual learning, and differentiation that are in line with modern educational theory. This study concludes that the Prophet Muhammad's teaching tradition is a rich and valid source of inspiration for the development of innovative learning methods in the modern era. The integration of the hadith treasury curated by scholars such as Abu Ghuddah with contemporary educational insights can give rise to an authentic, effective, and transformative model of Islamic education.